Analisis Strategi Pemasaran dalam Meningkatkan Tingkat Penjualan Hunian Kamar Atas Penginapan Gabelo Guest House Kota Bukittinggi (Lembaga Pengembangan Kinerja Dosen, 2025)
This research was motivated by the problems faced by Gabelo Guest House Bukittinggi, which experienced a decline in room sales from 2019 to 2021. The decrease was mainly caused by the lack of promotional activities, resulting in suboptimal occupancy rates. The purpose of this study is to analyze the marketing strategy applied by Gabelo Guest House through a strategic management approach and to formulate an appropriate marketing strategy as a guideline for business development. The method used is qualitative research with a descriptive approach. Data were obtained from observations, interviews, and documentation at Gabelo Guest House, and analyzed using the Internal Factor Analysis Summary (IFAS), External Factor Analysis Summary (EFAS), SWOT matrix, and weighted score tables. The results of the study indicate that marketing strategies should focus on improving friendly services for guests and travel agents in order to expand the market. In addition, the development and maintenance of the hotel’s garden area play an important role in supporting guests’ comfort and tranquility. The analysis results show a strength score of 2.28, a weakness score of 1.00, an opportunity score of 2.12, and a threat score of 0.94. The total score for IFAS was 3.22 and for EFAS 3.12. Based on these findings, the most influential and prioritized marketing strategy for Gabelo Guest House is the S-O (Strengths-Opportunities) strategy, which utilizes internal strengths to maximize external opportunities.